Molecular and functional dissection of LIGULELESS1 (LG1) in plants - Qin, Lei; Wu, Xintong; Zhao, Hang (Frontiers in Plant Science, 2023)
Plant architecture is a culmination of the features necessary for capturing light energy and adapting to the environment. An ideal architecture can promote an increase in planting density to achieve an increase in crop yield. A number of plant architecture-related genes have been identified by map cloning, quantitative trait locus (QTL) and genome-wide association study (GWAS) analysis. LIGULELESS1 (LG1) is belongs to the squamosa promoter-binding protein (SBP) family of transcription factors (TFs) that are key regulators for plant growth and development, especially leaf angle (LA) and flower development. The DRL1/2-LG1-RAVL pathway is involved in brassinosteroid (BR) signalling to regulate the LA in maize, which has facilitated the regulation of plant architecture through molecular breeding. Therefore, exploring the gene regulatory functions of LG1, especially its relationship with LA genes, can help achieve the precise regulation of plant phenotypes adapted to varied environments, thereby increasing the yield. This review comprehensively summarizes the advances in LG1 research, including its effect on LA and flower development. Finally, we discuss the current challenges and future research goals associate with LG1.